EFFECT OF POLLUTION ON PIN-TYPE POLYMERIC INSULATORS BY THE FINITE ELEMENT METHOD - Leite Neto, Antonio Francisco; Dias, Bruno Albuquerque; Diniz, Larissa; da Costa, Edson Guedes; Marcos, João Marcos Leal (Seven Editora, 2025)
The climatic conditions of an environment and its unpredictable changes can be a major problem in the sizing of long transmission lines, due to the constant exposure of its components to the various types of weather present in the environment. The accumulation of pollutants on the surface of insulators is one of the main factors contributing to insulation failures in transmission lines. This wear occurs because when it comes into contact with moisture, a thin conductive layer forms, changing the distribution of the electric potential and increasing the concentration of the electric field. Thus, it is relevant to analyze insulators in operation when they are subjected to adverse conditions imposed by the environment, which can lead to failures, damaging equipment, causing inconvenience and losses due to eventual shutdowns in the electrical power system. This work analyzes two topologies of pin-type polymeric insulators, voltage class of 15 kV, with the objective of analyzing the electrical behavior when the insulator is subjected to pollution. The analysis of the electric potential, electric field and current density in polymeric insulators is performed using computer simulation. A pollution layer is modeled on the surface of the insulators in order to investigate the influence of pollution on the operation of the insulators, with the variation of the conductivity and permittivity parameters it is possible to simulate pollution at different levels of criticality. From the results obtained, it was possible to observe the electrical characteristics of the two different topologies of polymeric insulators and to verify which is the best topology for the different levels of pollution. DOI: https://doi.org/10.56238/sevened2025.029-101